Lake Success : a novel - Shteyngart, Gary, 1972- (Random House, 2018)
"When his dream of the perfect marriage, the perfect son, and the perfect life implodes, a Wall Street millionaire takes a cross-country bus trip in search of his college sweetheart and ideals of youth. Myopic, narcissistic, hilariously self-deluded and divorced from the real world as most of us know it, hedge fund manager Barry Cohen oversees $2.4 billion in assets. Deeply stressed by an SEC investigation and by his 3 year-old-son's diagnosis of autism, he flees New York on a Greyhound bus in search of a simpler, more romantic life with his old college sweetheart, whom he hasn't seen or spoken to in years. Meanwhile, reeling from the fight that caused Barry's departure, his super-smart wife Seema--a driven first-generation American who craved a picture-perfect life, with all the accoutrements of a huge bank account--has her own demons to face. How these two imperfect characters navigate the Shteyngartian chaos of their own making is the heart of this biting, brilliant, emotionally resonant novel very much of our times"--